Intraocular Distribution and Kinetics of Intravitreally Injected Antibodies and Nanoparticles in Rabbit Eyes - Kim, Hyeong Min (Transl Vis Sci Technol, 2020)
PURPOSE: To investigate the intraocular distribution and kinetics of antibodies and nanoparticles in the experimental model. METHODS: Antibodies (whole IgG 149kDa, antigen-binding fragments 48.39 kDa) and four kinds of nondegradable nanoparticles (25, 50, 200, and 250 nm) were intravitreally injected in the right eye of New Zealand white rabbits. The average optical density and concentration were used to measure intraocular distribution and kinetics. RESULTS: After intravitreal injection, antibodies were distributed throughout the vitreous humor and eliminated gradually into anterior and posterior routes. Fluorescence intensity decreased 1 day after injection and was not detected 25 days after injection. The nondegradable nanoparticles migrated posteriorly to the retina 7 days after injection onward and anteriorly to the aqueous humor from 1 hour to 1 day after injection. The fluorescence intensity of the nanoparticles was relatively stable in the vitreous humor, compared to antibodies. Nanoparticles accumulated on the internal limiting membrane of the retina with no penetration into deeper retinal tissue, whereas the smaller size 25 nm nanoparticles passed across the ciliary body and moved into choroid, retina, and suprachoroidal space. A gradual decrease of nanoparticles by their sizes in the vitreous after 30 days after injection was described as the percentage ratio: 61.1% (25 nm), 69.1% (50 nm), 78.6% (200nm), and 85.3% (250 nm). CONCLUSIONS: Our study revealed the in vivo intraocular distribution and kinetics of antibodies and nanoparticles with diverse sizes and the result might help to develop newer intraocular drugs and drug delivery systems to treat retinal diseases. TRANSLATIONAL RELEVANCE: These experimental results can be valuable data for human research.